Isolation and analysis of citral from Cymbopogon citratus (DC) (Fam. Gramineae) - Ortega, Adolfo M. (Manila College of Pharmacy, University of the Philippines, 1988)
Extraction of the essential oil from Cymbopogon citratus (DC) Stapf by steam distillation using a Clevenger apparatus for oils lighter than water. A total of 2037 g. of the plant material was used in successive extraction of the oil. The oil yield was 4.95 mL (0.23%) based on the crude extract and after drying over anhydrous sodium sulfate, it became roughly 3.5 mL. The oil was stored in a tight, amber colored bottle in the refrigerator.
Thin layer chromatography was predominantly done (as a means of separation) on the oil to determine the best solvent system and the best type of silica gel to use. Other physical test such as refractive index was performed on the oil. Specific gravity, optical rotation were not obtained due to the relatively small volume of oil obtained. Also, analysis of the oil by IR spectra was done by the Institute of Chemistry, College of Science in UP Diliman to give the fingerprint of the oil.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, September 1988.
Keywords: Lemongrass; Tanglad